2016
DOI: 10.1016/j.celrep.2016.08.073
|View full text |Cite
|
Sign up to set email alerts
|

NAMPT-Mediated NAD+ Biosynthesis Is Essential for Vision In Mice

Abstract: SUMMARY Photoreceptor death is the endpoint of many blinding diseases. Identifying unifying pathogenic mechanisms in these diseases may offer global approaches for facilitating photoreceptor survival. We found that rod or cone photoreceptor-specific deletion of nicotinamide phosphoribosyltransferase (Nampt), the rate-limiting enzyme in the major NAD+ biosynthetic pathway beginning with nicotinamide, caused retinal degeneration. In both cases, we could rescue vision with nicotinamide mononucleotide (NMN). Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
195
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(205 citation statements)
references
References 75 publications
8
195
2
Order By: Relevance
“…These findings suggest that these sirtuins are individually dispensable under basal conditions. These findings are important, as we previously demonstrated that NAMPT-mediated NAD + biosyn-thesis is essential for retinal function and that SIRT3/SIRT5 may play important roles in NAD + -dependent retinal homeostasis under conditions of stress (Lin et al 2016). These results expand on our previous findings and clarify the role of various sirtuin family members in retinal survival and function.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…These findings suggest that these sirtuins are individually dispensable under basal conditions. These findings are important, as we previously demonstrated that NAMPT-mediated NAD + biosyn-thesis is essential for retinal function and that SIRT3/SIRT5 may play important roles in NAD + -dependent retinal homeostasis under conditions of stress (Lin et al 2016). These results expand on our previous findings and clarify the role of various sirtuin family members in retinal survival and function.…”
Section: Discussionmentioning
confidence: 86%
“…We examined multiple mice per genotype and present representative images. To assess retinal function, we performed electroretinography (ERG) with the UTAS-E3000 Visual Electrodiagnostic System running EM for Windows (LKC Technologies, Gaithersburg, MD), as described previously (Lin et al 2016), testing at least three mice per genotype. For statistical analysis of the ERG data, we used GraphPad Prism version 5.0f (La Jolla, CA) to perform a mixed two-way ANOVA (within-subjects factor, flash intensity; between-subjects factor, genotype).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, P7C3, a pro-neurogenic putative NAMPT activator (Pieper et al, 2010; Wang et al, 2014), is neuroprotective in animal models of Parkinson’s Disease and ALS (De Jesus-Cortes et al, 2012; Tesla et al, 2012). NAD-boosting regimens prevent and in some cases can reverse neuronal degeneration associated with hearing loss, prion toxicity, retinal damage, traumatic brain injury (TBI), and peripheral neuropathy (Brown et al, 2014; Dutca et al, 2014; Hamity et al, 2017; Lin et al, 2016; Vaur et al, 2017; Yin et al, 2014; Zhou et al, 2015). …”
Section: Effects Of Nad+ Boosters On Physiology and Health In Mouse Mmentioning
confidence: 99%
“…This is also true for NR, as NRKs are rate limiting in its conversion to NMN. Although administration of NMN protects from retinal photoreceptor degenerations induced by NAMPT deficiency or light exposure 102 , potential accumulation of NMN may be detrimental for glaucoma as NMN can participate in axon degeneration 103 (axon injury and activation of axon intrinsic degeneration pathways are central in glaucoma). Thus NAM may have better efficacy than NMN in glaucoma.…”
Section: Choice Of Nad Precursor and Safetymentioning
confidence: 99%